"Maiatzeko loreen eguneterako berba-aldiak": jatorrizko eskuizkribua eta 1885eko edizioa - Altzibar, Xabier (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1990)
This article aims to draw attention to the original text of the last work of a experienced Bizcayan writer, Juan José Moguel, since the first edition ofthis work appeared almost forty years after the death of the author. In fact, the edition was full of misprints, but on the other hand the editor or the person who was in charge of preparing the text made a lot of changes, consciously, in the morphological, lexical and graphical aspect. Most of the morphological changes are mistakes, a great deal of theam owing to misunderstanding, specially of Bizcayan forms. Many lexical forms of this dialect are also changed into Gipuzkoan, as the edition was made in Tolosa and presumably by a native of Gipuzkoa or having in mind readers from this province too. As for the graphical aspect, the edition doesn't pay attention to the uses of the author nor to the characteristics of the marquinese classic writers in this field, and therefore the changes aim to adapt the original text to the graphical uses ofthe Basque writings at the time of ninenteenth century Pizkundea, maybe prevailing. One of this adaptations, ŝ after a, e, o, u instead of the ss of the original text is incorrect, as the author uses it after i to represent the palato-alveolar (chicheante) fricative, /s/, but after a, e,o, u to represent the upper-alveolar sibilant, /ś/.